2008
DOI: 10.1525/cond.2008.110.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Drought on Annual Survival of the Mountain Plover in Montana

Abstract: I used a robust design to model the influence of age, sex, climate conditions, and chick body mass on the annual survival of the Mountain Plover (Charadrius montanus) in north-central Montana from [1995][1996][1997][1998][1999][2000][2001][2002][2003][2004][2005][2006]. I found evidence that chick age predicted body mass (i.e., log 10 (mass) = 0.03 × age + 1.02) and subsequently modeled juvenile survival as a function of body mass. Juvenile survival was similar for both sexes and was positively influenced by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Although we did not measure reproductive success in our study, selection for historical disturbances is likely related to increased plover reproduction and/or survival. Adult survivorship of mountain plovers breeding on black‐tailed prairie dog colonies in Montana increased in drought years and decreased in wet years (Dinsmore 2008). We found large patches with >35% bare soil occurred on burns and prairie dog colonies in dry years (2007–2008), whereas bare soil declined in all habitats following above‐average precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not measure reproductive success in our study, selection for historical disturbances is likely related to increased plover reproduction and/or survival. Adult survivorship of mountain plovers breeding on black‐tailed prairie dog colonies in Montana increased in drought years and decreased in wet years (Dinsmore 2008). We found large patches with >35% bare soil occurred on burns and prairie dog colonies in dry years (2007–2008), whereas bare soil declined in all habitats following above‐average precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…The role of drought as an ecological driver of plover population recruitment is further supported by the correlation of annual survival of adult Mountain Plovers with dry climatic conditions (Dinsmore 2008) and drought-induced recruitment of young (Wunder 2007). The Colorado and Montana nest survival studies differed in the actual metric that best described the relationship; the best-fitting daily precipitation metric in our study was an extended lack of precipitation (droughts when ≥ 10 days had passed with ≤ 1 mm total rainfall), whereas Dinsmore et al (2002) reported lower survival with rain events ≥ 2.54 cm.…”
Section: Daily Precipitation Depressed Nest Survival Of Mountainmentioning
confidence: 99%
“…Little is known about Mountain Plover migratory ecology or wintering ground locations. Differences amongst breeding populations in their migration patterns or winter locations could lead to sex-specific survival differences in adults, possibly explaining why annual survival is similar for males and females in a breeding population of Mountain Plovers in Montana (Dinsmore 2008).…”
Section: Discussionmentioning
confidence: 99%